Laryngeal and Vocal Characterization of Asymptomatic Adults With Sulcus Vocalis - Soares,Alex Bruno (2019)
Abstract Introduction Sulcus vocalis is defined as a longitudinal depression on the vocal cord, parallel to its free border. Its most marked characteristic is breathlessness, caused by incomplete glottal closure, in addition to roughness, due to the decrease in mucosal wave amplitude of the vocal cords. Vocal acoustic aspects, such as fundamental voice frequency, jitter, and shimmer, may also be altered in individuals with this type of laryngeal disorder. To assess the voice of individuals with sulcus vocalis, studies generally include a sample of subjects with vocal symptoms, excluding asymptomatic persons. To better characterize the vocal characteristics of individuals with sulcus vocalis, their asymptomatic counterparts must also be included. Objective Characterize the larynx and voice of asymptomatic adults with sulcus vocalis. Method A total of 26 adults, 13 with sulcus vocalis (experimental group) and 13 without (control group) were assessed. All the participants were submitted to suspension microlaryngoscopy, voice self-assessment, auditory perception and acoustic evaluation of the voice. Results Among the individuals with sulcus vocalis, 78% of the sulci were type I and 22% type II. Auditory perception assessment obtained statistically significant lower scores in individuals with sulcus vocalis compared with the control group, and a slight difference in the overall degree of hoarseness and roughness. No statistically significant intergroup diferences were found in self-reported voice or acoustic assessment. Conclusion Type I was the predominant sulcus vocalis observed in individuals without voice complaints, who may also exhibit slight changes in vocal quality and roughness.